Anti-Proliferative Compound Candidate of White Turmeric (Curcuma zedoaria) - Putu Oky Ari Tania; Candra Rini Hasanah Putri; Ayling Sanjaya; Titiek Sunaryati; Deddy Hartanto; Erlix R Purnama; Meivy Isnoviana (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2023)
Malignant disease or cancer progression burden the community after decades. This tumor formation or tumorigenesis involves cell proliferation. Protein Kinases (MAPK9s) is key proteins of regulating the growth and viability of cells physiologically and pathologically. Rhizomes of Curcuma zedoaria or zedoary or white turmeric is used as a health supplement. The aim of this study was to obtained candidate proteins for anti-proliferative using the docking method between the protein MAPK9 and the active compound obtained from the crude extract of white turmeric i.e. demethoxycurcumin, curcumenol and germacrone. The result s hows that complex MAPK-demethoxycurcumin have the lowest binding affinity -8.4 Kkal/mol, while MAPK-curcumenol was -8 Kkal/mol, and MAPK-Germacrone was -6.2 Kkal/mol, it determined the potential activity cell proliferation.